Insights of 6G and artificial intelligence-based internet-of vehicle towards communication - Madhusudhan Golla; Veena Kalludi Narasimhalah; Ajay Betur Puttappa (IAES International Journal of Artificial Intelligence (IJ-AI), 2023)
The significance of internet-of-vehicle (IoV) is spontaneously increasing with exponentially rising demands towards transportation system and road safety. At present, there are various number of scientific approaches which is meant for leveraging the communication performance in IoV, but yet the problem still exists over multiple attributes e.g. resource management, privacy, security, and service offloading. Such problems are anticipated to be solved by 6G services that offers better communication capabilities compared to its prior version of 5G. At the same time, the quality of communication system can be enhanced by artificial intelligence (AI), which is capable of solving complex real-world problems. Therefore, this manuscript offers an insight towards strength and weakness of existing 6G based study model as well as AI-based solution in order to contribute towards highlighting an essential research gap that could directly offer better insight towards future planning towards improving communication in IoV.